6,6′-Dimethoxy-2,2′-[(hexane-1,6-diyldioxy)bis(nitrilomethylidyne)]diphenol - Dong, Wen-Kui (International Union of Crystallography, 2008)
In the title compound, C(22)H(28)N(2)O(6), strong intramolecular O—H⋯N hydrogen bonds and weak intermolecular C—H⋯O hydrogen bonds stabilize the three-dimensional supramolecular structure.